Circulating endothelial cells in pulmonary hypertension - Bull, Todd M.; Golpon, Heiko; Hebbel, Robert P.; Solovey, Anna; Cool, Carlyne D.; Tuder, Rubin M.; Geraci, Mark W.; Voelkel, Norbert F. (Thrombosis and Haemostasis, 2003)
The pulmonary endothelium plays a significant role in the pathobiology of Primary Pulmonary Hypertension. A number of diseases, related by a history of vascular injury, are associated with increased numbers of circulating endothelial cells (CECs). We hypothesized that patients with pulmonary hypertension would also have an increased number of circulating endothelial cells due to the high pressures and increased shear stress present within the pulmonary vasculature. We isolated the CECs from 14 patients with pulmonary hypertension, (5 primary and 11 secondary) and compared them to the cells from 12 normal controls. There was a significant increase in the number of CECs in peripheral blood in patients with both PPH and secondary pulmonary hypertension (SPH) when compared to normal volunteers (33.1 +/- 1.9 PPH and 27.2 +/- 6.9 SPH vs. 3.5 +/- 1.3 {controls}, p < 0.001). The number of circulating endothelial cells in the patient’s peripheral blood correlated significantly with the systolic, diastolic and mean pulmonary artery pressures of the individual. Approximately 50% of the CECs from patients with pulmonary hypertension expressed CD36, a marker of microvascular origin and 25% expressed E-selectin, a marker of endothelial cell activation. Although the origin of the CECs in patients with PH requires further investigation, one possible source is the pulmonary vasculature, and in patients with plexogenic pulmonary hypertension, the plexiform lesions. CECs may provide a non-invasive mean of accessing cells important to the pathobiology of severe pulmonary hypertension.
Keywords: Circulating endothelial cells; plexiform lesion; angiogenesis; primary pulmonary hypertension